Beyond church and state : democracy, secularism, and conversion - Scherer, Matthew., 1977- (USA : Cambridge University Press, 2013)
"Secularism is often imagined in Thomas Jefferson's words as 'a wall of separation between Church and State'. This book moves past that standard picture to argue that secularism is a process that reshapes both religion and politics. Borrowing a term from religious traditions, the book goes further to argue that this process should be understood as a process of conversion. Matthew Scherer studies Saint Augustine, John Locke, John Rawls, Henri Bergson and Stanley Cavell to present a more accurate picture of what secularism is, what it does, and how it can be reimagined to be more conducive to genuine democracy"--
Machine generated contents note: Introduction: beyond the separation of church and state: secularism as conversion; 1. The authorized narrative and crystalline structure of conversion in Augustine's Confessions; 2. Toleration and conversion in Locke's letters: it is 'above all things necessary to distinguish'; 3. The crystalline structure of conversion: Henri Bergson's Two Sources; 4. Saint John (Rawls), the miracle of secular reason; 5. The wish for a better life: Stanley Cavell's critique of the social contract; Conclusion: 6. From Supernovas into The Deep: secularism as conversion, a conversion of secularism
Includes bibliographical references and index.
Keywords: Secularism; Religion and politics; Political Science / History & Theory